Identificação de estratégias farmacológicas e não farmacológicas para a melhoria da vida sexual em mulheres - (:unkn) unknown (UNIFAP - Universidade Federal do Amapá, 2023)
Sexual activity is part of women's quality of life, from the beginning of menstruation to menopause, during this period there may be situations that affect the satisfaction of this cycle, bringing discomfort, contempt, and libido absenteeism, such as preexisting diseases, medication use, anxiety, psychological problems, even menopause itself due to hormonal fluctuations, among other reasons. The objective of this work was to investigate the difficulties that accompany these women and the possible alternatives they seek to select these problems, whether in pharmacological or non-pharmacological areas, to analyze the socio epidemiological conditions of women with an active sex life in the state of Amapá. The research was carried out through an online questionnaire answered by women from the age of eighteen and with an active sex life, including those who are in the climacteric process. The results showed that most of the interviewed women have problems related to the satisfaction of their sexual life, mainly with the lack of natural lubrication, which can be influenced by the use of medication, mainly analgesics or related to the treatment of chronic diseases. No woman reported the use of drugs for lack of libido and lubrication, however, most of them look for nonpharmacological strategies to solve the problem, such as the use of erotic products. All interviewees had high school or higher education, most had between 1 and 3 children, and reported having a dialogue with their partners about it. This research was able to clarify particularities of female sexual life and provide information on women's health for future studies.
Keywords: Sexualidade feminina; Disfunção sexual feminina; Libido; CNPQ::CIENCIAS DA SAUDE::FARMACIA; ODS 3 – Saúde e bem-estar